Transcriptomics of circulating neutrophils in dairy cows with subclinical hypocalcemia - Zhang, Bingbing; Ma, Xinru; Huang, Baoyin; Jiang, Qianming; Loor, Juan J.; Lv, Xinquan; Zhang, Wei; Li, Ming; Wen, Jianan; Yin, Yufeng; Wang, Jingjing; Yang, Wei; et al. (Frontiers in Veterinary Science, 2022)
Hypocalcemia is closely associated with inflammatory diseases in dairy cows. Recent research has underscored the key role of calcium in the adaptations of the innate immune system. The main objective in the present study was to compare the transcriptome profiles and analyze differences in the expression of neutrophil (PMNL) immune function-related genes and calcium binding-related genes in hypocalcemic cows. At 2 days postpartum, a concentration greater than 2.10 mmol Ca2+/L was used to classify cows as controls (CON), and a concentration less than 2.00 mmol Ca2+/L used to classify cows as low-calcium (LCAL) (n = 8 in each group). A routine medical examination was conducted by the attending veterinarian to ensure there were no other complications and that the blood β-hydroxybutyrate was <1.2 mmol/L. Blood was collected from the tail vein (20 mL) to isolate PMNL, and 5 cows in each group were used for RNA sequencing and statistical analysis of gene expression differences. Transcriptome RNA-seq sequencing analysis was via omicsstudio using the R package edgeR. GO and KEGG enrichment analysis were used for bioinformatics. The remaining 3 cows in each group were used for validation of RNA sequencing data via quantitative PCR, which confirmed the observed responses. Compared with CON, 158 genes in LCAL were significantly up-regulated and 296 genes were down-regulated. The downregulation of Interleukin-12 (CXCL12), Tubulin beta chain (TUBB1), L1 cell adhesion molecule (L1CAM), and Myeloperoxidase (MPO) indicated a decrease in immune function of PMNL in LCAL cows. The decreased expression of calcium-binding pathway-related genes in PMNL of LCAL cows indicated a decrease in immune function of PMNL likely related to calcium ions. For example, cartilage acid protein 1 (CRTAC1) and calcium/calmodulin-dependent kinase 4 (CAMK4) were significantly reduced in LCAL cows. The upregulation of Cyclin dependent kinase inhibitor 1A (CDKN1A), Perforin 1 (PRF1), and Homeodomain interacting protein kinase 3 (HIPK3) indicated that LCAL led to greater cell apoptosis and senescence. Overall, the analyses indicated that the reduction in PMNL immune function during hypocalcemia is associated with downregulation of intracellular Ca2+ related genes and upregulation of genes controlling apoptosis and senescence.